2021
DOI: 10.1007/s11126-021-09899-7
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 on Provider Perceptions of Telemental Health

Abstract: The present study was designed to assess mental health provider attitudes and perceptions of telemental health (TMH) prior to and during the COVID-19 Pandemic, as well as the nature of their TMH utilization. The study aimed to gather information about positive and negative attitudes towards TMH, perceptions and correlates based on the modality of care, and beliefs about the overall effectiveness of TMH as compared to face-to-face care. The current study is part of a larger mixed methods project utilizing a rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 49 publications
3
19
0
Order By: Relevance
“…One study found that only 29% of clinical psychologists used telehealth for a portion of their caseload prior to the pandemic and, within weeks of the pandemic, over 80% of the sample reported using telehealth for nearly their entire caseload (Sammons et al, 2020 ). When faced with the necessity to use telehealth, some evidence suggests clinicians experienced negative feelings including anxiety (Doorn et al, 2021 ; Doran & Lawson, 2021 ). A qualitative study found about a quarter of the sample’s clinicians described an initial negative and pessimistic reaction to their transition to telehealth, citing concerns about the quality of care and the ability to manage complex cases and crisis situations (Hersch et al, 2022 ).…”
Section: Using Exposure To Overcome Hesitancymentioning
confidence: 99%
See 2 more Smart Citations
“…One study found that only 29% of clinical psychologists used telehealth for a portion of their caseload prior to the pandemic and, within weeks of the pandemic, over 80% of the sample reported using telehealth for nearly their entire caseload (Sammons et al, 2020 ). When faced with the necessity to use telehealth, some evidence suggests clinicians experienced negative feelings including anxiety (Doorn et al, 2021 ; Doran & Lawson, 2021 ). A qualitative study found about a quarter of the sample’s clinicians described an initial negative and pessimistic reaction to their transition to telehealth, citing concerns about the quality of care and the ability to manage complex cases and crisis situations (Hersch et al, 2022 ).…”
Section: Using Exposure To Overcome Hesitancymentioning
confidence: 99%
“…These conditions provided the opportunity for informal exposure exercises that resulted in adaptive changes in behavior and perspectives. Direct experience with telehealth resulted in reduced negative reactions to telehealth (Doorn et al, 2021 ; Doran & Lawson, 2021 ). Qualitative studies illustrated how clinicians faced their telehealth concerns during the pandemic and committed to behavior change that ultimately enriched the experience of their patients and themselves (Hersch et al, 2022 ; Uscher-Pines et al, 2020 ).…”
Section: Using Exposure To Overcome Hesitancymentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of the pandemic, the urgent and rapid adoption of TMH created wide variability across TMH utilization and protocols [1]. Research evaluating the clinical efficacy and feasibility of specific TMH modalities used in clinical care suggests that synchronous video conferencing is preferable to telephone [8][9][10] and is comparable to face-to-face treatment delivery across a wide range of populations, settings, and diagnoses [11][12][13]. However, a recent review of evaluation approaches for TMH programs found that there is inconsistency in assessment methods and no clear gold standard for TMH program measurement [14].…”
Section: Introductionmentioning
confidence: 99%
“…Some mental health providers’ caseloads increased by 25–50% during the pandemic with patient surges as high as 6,558% ( 1 , 3 ). Telemedicine revolutionized the delivery of evidence-based mental health care ( 4 ), and proved to be a dependable solution that 90% of providers surveyed intend to use beyond the resolution of COVID-19 ( 5 ). It is imperative to understand how mental health providers deliver remote services to inform and sustain post-pandemic TMH care models.…”
Section: Introductionmentioning
confidence: 99%